Computational Study of Surface Deposition and Gas Phase Powder Formation during Spinel Chemical Vapor Deposition Processes - Wang, H.; Stern, H.; Chakraborty, D.; Bai, H.; DiFilippo, V.; Goela, J.; Pickering, M.; Gale, Julian (American Chemical Society, 2013)
Chemical vapor deposition (CVD) processes are often employed to produce high quality materials. In some applications, a relatively fast deposition rate is required to produce thick pieces of material, e.g., on the order of centimeter, in an economical manner. However, in some processes the formation of solid nuclei or powder in the gas phase can be a major obstacle to increasing the deposition rate. The homogeneous powder formation reaction can compete with the surface deposition reaction and consume the gas phase reactants, thus reducing the available material to grow on the substrate surface. Understanding the thermodynamics as well as kinetics of these two competing reactions helps elucidate the reaction conditions that best reduce powder formation and increase deposition rate. As an example where gas phase powder formation can significantly limit the surface deposition rate CVD growth of spinel (MgAl2O4) is investigated. In this CVD process, reverse water gas shift (rWGS) is employed to generate water, which reacts with either chlorides or fluorides of magnesium and aluminum to produce spinel. Density functional theory (DFT) was used to study the thermodynamics of surface reactions of spinel deposition. This study shows that the surface reaction to form spinel is thermodynamically favorable. However, the spinel deposition could be limited by its surface kinetics and/or competition for reactants with gas phase powder formation. We have employed molecular dynamics (MD) with a reactive force field (ReaxFF) to simulate gas phase rWGS and powder formation. These simulations show that the reactants’ residence time should be minimized to reduce powder formation. A comparison of magnesium and aluminum chlorides with their corresponding fluorides indicates that fluorides are better in reducing powder formation.